Exploring the relationship between climate change and violent conflict. Issue 3 (3rd July 2018) - Koubi, Vally
ABSTRACT: Does climate change lead to violent conflict? This article reviews the existing literature connecting climatic conditions to conflict. It finds that the existing literature has not detected a robust and general effect from climate to conflict onset. Moreover, there exists scientific agreement that climatic changes can contribute to conflict under some conditions and through certain pathways. In particular, the recent literature offers considerable suggestive evidence that climatic changes can lead to conflict in countries and/or regions, which are dependent on agriculture, host politically excluded groups, and have ineffective institutions. Future research should focus not only on understanding of the pathways and contexts in which climatic changes are most likely to increase or exacerbate the risk of conflict but also work to understand the mechanisms by which climate variability and change might cause conflict.